2021
DOI: 10.1007/s43630-021-00047-5
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of mineralisation in mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) and photobiomodulation (PBM) both offer significant therapeutic potential in regenerative medicine. MSCs have the ability to self-renew and differentiate; giving rise to multiple cellular and tissue lineages that are utilised in repair and regeneration of damaged tissues. PBM utilises light energy delivered at a range of wavelengths to promote wound healing. The positive effects of light on MSC proliferation are well documented; and recently, several studies have determined the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…ALAD alone (100-ALAD) also increased the production of ROS at 10 and 20 min ( Figure 6 A), whereas in HOB, ALAD-PDT significantly stimulated the ROS after 30 min in respect to basal concentrations of ROS in control cells ( Figure 6 B). The ROS levels in both cells showed a similar result to the control group by 1 h after the photodynamic protocol, and also remained at the basal level at 24 h. Studies have shown that high levels of ROS can cause cell death, but ROS are also important mediators of intracellular signaling [ 29 , 30 , 31 ]. Although the detailed mechanism has yet to be revealed, Kushibiki et al showed that PDT promotes murine osteoblasts differentiation via AP-1 that is upregulated by high ROS production [ 24 ].…”
Section: Resultsmentioning
confidence: 65%
“…ALAD alone (100-ALAD) also increased the production of ROS at 10 and 20 min ( Figure 6 A), whereas in HOB, ALAD-PDT significantly stimulated the ROS after 30 min in respect to basal concentrations of ROS in control cells ( Figure 6 B). The ROS levels in both cells showed a similar result to the control group by 1 h after the photodynamic protocol, and also remained at the basal level at 24 h. Studies have shown that high levels of ROS can cause cell death, but ROS are also important mediators of intracellular signaling [ 29 , 30 , 31 ]. Although the detailed mechanism has yet to be revealed, Kushibiki et al showed that PDT promotes murine osteoblasts differentiation via AP-1 that is upregulated by high ROS production [ 24 ].…”
Section: Resultsmentioning
confidence: 65%
“…The combined use of mesenchymal stem cells (MSCs) and photobiomodulation (PBM) offers strategies with great therapeutic potential for regenerative medicine. 50 In this study, we successfully demonstrated the effect of 810 nm low-intensity NIR light on bone regeneration, and elucidated the mechanism by which light activates the BMP signaling pathways by promoting the ubiquitin-dependent degradation of CRY1, providing a novel clinical application of non-invasive NIR treatment in bone defects (Fig. 6 ).…”
Section: Discussionmentioning
confidence: 79%
“…(ii) When considering the addition of nanoparticles, the unique properties of nanoparticles should be considered, such as gMPs and pMPs with different degradation rates for sequential drug release in hydrogel delivery systems [ 70 ] and the loading of metal oxides for the continuous delivery of Mg 2+ [ 69 , 73 ]. In addition, studies on functionalized nanoparticles should be discussed; for example, NIR has better tissue penetration [ 59 ], and even the potential of NIR to induce osteogenic differentiation of MSCs has been reported [ 88 ], and its ability to penetrate the patient’s scalp to irradiate cranial defects in clinical practice deserves to be evaluated. NIR likewise provides inspiration as to whether upconverting nanoparticles can be introduced for the preparation of NIR-responsive hydrogel systems.…”
Section: Discussionmentioning
confidence: 99%